First 'Highly Cited Researcher’ in Singapore in the field of Economics and Business - Singapore Management University (Institutional Knowledge at Singapore Management University, 2019)
Singapore Management University’s (SMU) business school dean, Professor Gerard George, has been globally recognised as a ‘Highly Cited Researcher’ in the field of Economics and Business in 2019. Professor George, who is Lee Kong Chian Chair Professor of Innovation and Entrepreneurship, and Dean of SMU’s Lee Kong Chian School of Business, is the first business professor in Singapore to have received this accolade which recognises the significant and global impact of his research in academia.